Pengaruh Pemotongan Akar Tanaman Air Terhadap Penurunan BOD dan COD Limbah Domestik Dengan Metode Fitoremediasi - Yayok Suryo Purnomo; Nur Amalia Anggraini (Prosiding ESEC, 2022)
The kafe business experienced an increase of 16-18% in 2019 so that the waste generated also increased. Kafe waste has the same characteristics as domestic liquid waste with some characteristics being BOD, COD and fats. The exudate produced by plant roots is beneficial for microbes in helping to decompose organic matter. Thus, the purpose of this study was to determine the effect of cutting the roots of aquatic plants on the removal of BOD and COD levels in domestic waste and their effect on the growth of the number of microorganisms. In this study, two stages were used. The first stage is the pre-treatment stage starting from plant propagation, acclimatization, range finding test (RFT), cutting roots (with variations of 0%, 25% and 50%) and using Grease trap to remove oil and fat content. Then the core research stage is the removal of BOD and COD using the phytoremediation method with water hyacinth. From this research, it was found that the variation of plant stems and 50% root prunning on the 25th day had the most effective BOD and COD removal capabilities, namely 95.60% for BOD removal and 93.37% for COD removal. In addition, the results of this study also prove that there is an influence between the treatment of cutting plant roots and the growth of the number of microbes. This is evidenced by the large number of microbes in the 50% root cutting treatment, which is 101.24 mg/L